Physical activity, healthy lifestyle, and subjective wellbeing in people with type 2 diabetes: testing the efficacy of an exercise program - Cid, Luís; Monteiro, Diogo; Mendes, Romeu; Cláudio, Filipa; Bento, Teresa; Jacinto, Miguel; Couto, Nuno; Duarte-Mendes, Pedro (Frontiers in Aging, 2025)
IntroductionThis work aimed to first validate the Portuguese version of the FANTASTIC questionnaire that allowed the assessment of lifestyle behaviors through a sample comprising 562 Portuguese subjects; second, through a quasi-experimental study, we tested the effectiveness of a physical exercise program designed specifically for people with type 2 diabetes based on subjective wellbeing and lifestyle changes.MethodsFor 9 months, a total of 31 subjects (14 males and 17 females with type 2 diabetes aged between 58 and 79 years) were involved in a physical exercise program of moderate intensity three times per week for 75 min each session; the program included a combination of aerobic, resistance, agility, balance, and flexibility exercises (Diabetes em Movimento).ResultsRegarding the first goal of this study, the results show a reliable factorial solution with nine factors and 27 items from the FANTASTIC questionnaire. With regard to the second goal of this study, the results indicate that subjects involved in the exercise program show significantly improved positive affect, satisfaction with life, physical activity, sleep, stress, and nutrition behaviors, in addition to significantly diminished negative affect. However, these results should be interpreted with some caution as our study did not have a control group and the sample was one of convenience, which limits the capacity of inference of the results.ConclusionThe present results support evidence confirming the positive effects of Physical Exercise through the Diabetes em Movimento® program to foster SWB and promote healthier lifestyle behaviors among T2D subjects. Therefore, we intend to conduct further studies in the future to consolidate the findings of the present study.